Welfare Analysis of Regulating Mobile Termination Rates in the U.K.1. (December 2015) - Harbord, David; Hoernig, Steffen
Abstract : We develop a calibrated simulation model of the U.K. mobile telephony market and use it to analyze the effects of reducing mobile termination rates (MTR's) as recommended by the European Commission. We find that reducing MTR's is likely to increase both consumer surplus and networks' profits. Depending on the strength of call externalities (i.e., benefits to the recipient of a call), social welfare may increase by as much as £1 billion to £4.6 billion per year. We also use the model to estimate the welfare effects of the 2010 merger between Orange and T‐Mobile and find that the merger led to a substantial reduction in consumer surplus.